Tingkat Kepuasan Konsumen dalam Menggunakan Smartphone Merek Xiaomi pada Mahasiswa Politeknik Negeri Bengkalis - Eko Darmawan; Suharyono Suharyono (Politeknik Negeri Bengkalis, 2019)
A satisfication of customer is determined from customer perception on performance product or services to satisfy customer want. This research consign to knowing customer standard satisfy from using Xiaomi brand smarthphone of Bengkalis State Polytechnic Students. The type of research that use in this case as quantitative by spreading a questionner to 100 respondent people by using vote sample metode non